Intoleransi Keagamaan dalam Framing Surat Kabar Kompas - Enjang Muhaemin; Irfan Sanusi (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2019)
Indonesia is known as a multi-religious country in which there are various religions. United in diversity, and harmony in diversity becomes a key word that can no longer be contested. The intolerant attitude of any religious group can be a trigger for conflict which endangerthe integrity of the NKRI. This study aims to determine the framing of the Kompas newspaper in discussing and packaging the discourse of religious intolerance and religiosity in Indonesia. This research method uses Robert N. Entman's framing analysis, which focuses the study on the prominence of the framework of thought, perspective, concepts, and claims of media interpretation in interpreting the object of discourse. Research is expected to be able to stimulate the public to be more critical in understanding the various news constructed by journalists. The results showed that Kompas defined the problem of religious intolerance and diversity in Indonesia as a matter of religion, social, political, educational, and nationalism. However, Kompas generally defines it as a matter of understanding religion and weakening the attitude of nationalism. Kompas news considers the source of the cause to be more dominant because of superficial, partial, and little religious understanding. Kompas concludes that intolerance is a serious threat that could endanger the NKRI. The recommendations offered include the government being demanded to be assertive, fast, and not political. Religious leaders are recommended to build dialogical communication in an intense and continuous manner, and educate the public to always raise awareness of deep, moderate, and not extreme religiosity.Indonesia dikenal sebagai negara multiagama yang di dalamnya terdapat beragam agama. Bersatu dalam keragaman, dan harmoni dalam perbedaan menjadi kata kunci yang tak bisa lagi diganggu gugat. Sikap intoleran dari kelompok penganut agama manapun bisa menjadi pemicu konflik yang membahayakan keutuhan NKRI. Penelitian ini tujuan mengetahui pembingkaian surat kabar Kompas dalam mengupas dan mengemas wacana intoleransi keagamaan dan keberagamaan di Indonesia. Metode penelitian ini menggunakan analisis framing Robert N. Entman, yang memokuskan kajian pada penonjolam kerangka pemikiran, perspektif, konsep, dan klaim penafsiran media dalam memaknai objek wacana. Penelitian diharapkan mampu menstimuli masyarakat untuk kian kritis dalam memahami beragam berita yang dikonstruksi wartawan. Hasil penelitian menunjukkan, Kompas mendefinikan masalah intoleransi keagamaan dan keberagamaan di Indonesia sebagai masalah agama, sosial, politik, pendidikan, dan nasionalisme. Namun Kompas umumnya lebih mendefinisikan sebagai masalah pemahaman agama dan melemahnya sikap nasionalisme. Berita-berita Kompas menganggap sumber penyebabnya lebih dominan karena pemahaman agama yang dangkal, parsial, dan tidak mendalam. Kompas menyimpulkan intoleransi merupakan ancaman serius yang bisa membahayakan NKRI. Rekomendasi yang ditawarkan di antaranya pemerintah dituntut tegas, cepat, dan tidak berbau politis. Para tokoh agama direkomendasikan membangun komunikasi dialogis secara intens dan kontinyu, dan mendidik masyarakat untuk selalu meningkatkan kesadaran keberagamaan yang mendalam, moderat, dan tidak ekstrem.